MODERN APPROACH OF ZAKAT AS AN ECONOMIC AND SOCIAL INSTRUMENT FOR POVERTY ALLEVIATION AND STABILITY OF UMMAH - Wan Yusoff, Wan Sulaiman (I-iECONS e-proceedings, 2023)
The modern approach to zakat institution is a significant economic and social instrument for the poverty alleviation and stability of the Muslim Ummah. This paper highlights a wider scope of understanding the term "Poverty" and discusses how zakat institution can play an important role to alleviate the status of poverty in Muslim countries in the modern world. The main task of this paper is to use zakat institution to serve as a pool of resources for the economic and social development of the Ummah beginning with those who most needy. In this regard, zakat funds can be utilized for the development of resources especially concentrate in the area of human capital development for the long-term rather than short-term relief for those in need and at the same time, prevent the zakat revenues from diversion to undesired directions (Vision of IDB 1440H). We should aim at using zakat fund as a means of providing assistance that will have a long-lasting effect. Zakat institution should have long-term programme to teach the poor and needy know how to catch fish rather than every year we merely provide them with fish to eat.